Efektivitas Penggunaan Video Animasi dalam Meningkatkan Pemahaman Siswa terhadap Materi Perubahan Wujud Benda di Sekolah Dasar - Rizky putri L; Ibnu Muthi (STAI YPIQ BAUBAU, SULAWESI TENGGARA, 2025)
This study aims to examine the effectiveness of using animated video media in improving elementary school students’ understanding of the material of changes in the form of objects, which includes the process of melting, freezing, evaporating, condensing, and sublimating. The material is often difficult for students to understand because it is abstract and cannot always be observed directly. This research uses a qualitative method with a library research approach, where data is collected and analyzed from various reliable sources such as accredited scientific journal articles, books, and previous research results. The analysis technique used refers to the Miles and Huberman model, namely data reduction, data presentation, and conclusion drawing. The results of the study show that the animated video media can improve students’ cognitive understanding through visualization of complex processes, strengthen information retention, and reduce common misconceptions. In addition, this media is also proven to increase students’ motivation, interest in learning, and participation in learning. The effectiveness of animated videos is greatly influenced by the quality of visual design, narration, appropriate duration, and their integration in learning activities such as discussions or experiments. Despite challenges such as limited facilities and teacher training needs, strategic solutions can be implemented to optimize the use of this media. Thus, animated videos can be an innovative and relevant strategic alternative in science learning in elementary schools, especially in conveying abstract concepts in a concrete and fun way.